An Intelligent Framework Prototype for Monitoring Students in Virtual Classroom - Ashutosh Satapathy; Jenila Livingston L. M (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Virtual classroom is one of the fastest growing educational technologies used by many industries and institutions. Today, Voice over Internet Protocol (VoIP) cloud is become a most accepted replacement to different virtual classroom technologies such as internet chat, internet radio, web conferencing, traditional video conferencing and peer to peer VoIP calls. It provides greater flexibility, reliability and cost efficient telecommunication features and operates on comparatively lesser bandwidth. Involvement of new technology in virtual classroom makes it more reliable to teachers and students. Still it follows traditional methods to monitor students by invigilator whether it may be inside the classroom or home study. A secure framework for virtual classroom is developed to not only monitor student’s activities continuously but also the amount of time spent by each student and provide security against unsecure unauthorized login. An effective monitoring System based on Liveness Face Detection techniques is proposed to add more flexibility to conduct virtual classroom and also increases the level of securities of each student’s accounts.